Fatal case of newborn Lassa fever virus infection mimicking late onset neonatal sepsis: a case report from northern Nigeria - Taofik Oluwaseun Ogunkunle; Surajudeen Oyeleke Bello; Chinwe Immaculata Anderson; Rashida Musa; Rasaq Olaosebikan; Abdulazeez Imam (BMC, 2020)
Abstract Background Lassa fever is a zoonotic viral infection endemic to the West Africa countries. It is highly fatal during pregnancy and as such reports of neonatal onset Lassa fever infections are rare in scientific literature. We report a fatal case of Lassa fever in a 26-day-old neonate mimicking the diagnosis of late-onset neonatal sepsis. Case presentation The patient is a 26-day-old neonate who was admitted with a day history of fever, poor feeding, pre-auricular lymphadenopathy and sudden parental death. He was initially evaluated for late onset neonatal sepsis. He later developed abnormal bleeding and multiple convulsions while on admission, prompting the need to evaluate for Lassa fever using reverse transcription polymerase chain reaction (RT-PCR). He died 31 h into admission and RT-PCR result was positive for Lassa fever. Conclusions Neonatal Lassa fever infection is highly fatal and can mimic neonatal sepsis. High index of suspicion is needed particularly for atypical presentations of neonatal sepsis in Lassa fever endemic areas.